Exploring the freshwater cladocera (Pleuroxus spp.) as new potential live feed in aquaculture - Amirah Yuslan; Hidayu Suhaimi; Nizalmie Azani; Wong, Wey-Lim; Nadiah W. Rasdi (Penerbit Universiti Kebangsaan Malaysia, 2024)
In freshwater lakes, cladocera play a crucial role in the food chain, as they are the primary source of nutrition for nearly all aquatic species. Pleuroxus spp. are very suitable for aquaculture due to their ease of handling, rapid growth, non-selective filter feeder, high nutritional value, and remarkable ability to adapt to many environmental conditions. Silver barbs are in high demand in the aquaculture business due to their excellent flavours and rapid development rate. In this study, Pleuroxus spp. was cultured in a control condition with water quality maintained at the room temperature of 26 ± 1 °C and pH of 7.0 ± 0.5. Five treatments of Pleuroxus spp. were prepared, which comprised of T1 (control) = unfed, T2 = coffee grounds, T3 = corn flour, T4 = wheat flour, and T5 = sugarcane waste. Pleuroxus spp. were fed with a selected diet solutions at a concentration of 0.5 g/L daily. The result shows that Pleuroxus spp. given T3 (24.88 ± 5.48 ind/mL) had a greater population density than T4 (22.13 ± 4.83 ind/mL), T2 (21.06 ± 5.27 ind/mL), and T5 (20.56 ± 4.92 ind/mL) dietary treatments. Pleuroxus spp. given T3 had the greatest survival rate (97.9 ± 9.8%) when compared to other diets, T4 (86.81 ± 19.07%), T2 (82.71 ± 16.56%), and T5 (75.00 ± 21.08%). Silver barb showed the highest amount of daily weight gain in treatment T3 (0.11 ± 0.001 mg/days; p < 0.05) compared with other dietary treatments. The maximum specific growth rate (SGR) (%) was achieved when fed with T3 (13.37 ± 0.02%; p < 0.05). The feed conversion ratio (FCR) was shown to be significantly different (p < 0.05). The FCR of larvae fed with different nutritional treatments ranged from 1.22 to 4.12, depending on the treatment. In comparison to other diets, the T3 treatment (1.22 ± 0.03) achieved the highest FCR ratio. In short, pre-feeding of zooplankton with prospective diets has built a baseline of improved aquaculture feeding procedures that may be employed in the future aquaculture businesses.